THE INFLUENCE OF RELATIONSHIP MARKETING TOWARDS TAXPAYER’S SATISFACTION IN TAX AMNESTY PROGRAM - Andrian Haro (Econosains Jurnal Online Ekonomi dan Pendidikan, 2018)
The objective of this research is to examine the influence of relationship marketing which consist of trust, commitment, and communication toward taxpayer’s satisfaction in tax amnesty program. By using the purposive sampling method, the research sample is taxpayers who have a NPWP and registered in tax amnesty program. Only 48 respondents who is qualified as the research sample. Multiple liniear regression was used to analyze the data and to test the research hypotheses through SPSS. The result shows there is no influence between trust toward taxpayer’s satisfaction in tax amnesty program. Meanwhile, commitment and communication have an influence on taxpayer’s satisfaction in tax amnesty program.